2016
DOI: 10.1021/acs.jafc.5b05853
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Metabolism of Flufiprole in Rat and Human Liver Microsomes

Abstract: The enantioselective metabolism of flufiprole in rat and human liver microsomes in vitro was investigated in this study. The separation and determination were performed using a liquid chromatography system equipped with a triple-quadrupole mass spectrometer and a Lux Cellulose-2 chiral column. The enantioselective metabolism of rac-flufiprole was dramatically different in rat and human liver microsomes in the presence of the β-nicotinamide adenine dinucleotide phosphate regenerating system. The half-lives (t1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…These results demonstrated that the penetration process of the SC could not provide any enantiomer selectivity, which also has been illustrated by molecular simulation results, presented in Figure 3. Furthermore, as was shown might be attributed to the competitive elimination of enantiomers under the action of metabolizing enzyme in the body as previous reports (Lin et al, 2016).…”
Section: In Vivo Permeation Studysupporting
confidence: 73%
“…These results demonstrated that the penetration process of the SC could not provide any enantiomer selectivity, which also has been illustrated by molecular simulation results, presented in Figure 3. Furthermore, as was shown might be attributed to the competitive elimination of enantiomers under the action of metabolizing enzyme in the body as previous reports (Lin et al, 2016).…”
Section: In Vivo Permeation Studysupporting
confidence: 73%
“…Competitive inhibition, transformation, and interaction between stereoisomers may lead to the generation of stereoselective metabolism in organisms. Lin et al 34 found that the metabolism of flufiprole within RLMs and HLMs has enantioselectivity. Zhan et al 35 presented that acetofenate was quickly metabolized to acetofenate-alcohol and the metabolic process was significantly enantioselective with preferential degradation of (−)-acetofenate and formation of (−)-acetofenate-alcohol in rabbit liver microsomes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…On the contrary, the V max of S ‐(+)‐fipronil (447 ± 19 pmol/min/mg protein) in the human liver microsome was higher than that of R ‐(−)‐fipronil (300 ± 8 pmol/min/mg protein), and the CL int values were also not significantly different for the enantiomers (Carrao, Dos Reis Gomes, et al, 2019). Alternative enantioselective metabolism of flufiprole, another phenylprazole insecticide, in rat and human liver microsomes was observed, that is, selectively metabolized R ‐(−)‐fipronil in rat but S ‐(+)‐fipronil in human microsome (Lin et al, 2016). Different enantioselective metabolic behaviors observed in different organisms are likely due to the different compositions and contents of metabolizing enzymes among species (Arora et al, 2015; Narimatsu et al, 2000).…”
Section: Resultsmentioning
confidence: 99%